Possibilities of Using the Likert’s Scale — Basic Principles of Application in Pedagogical Research and Demonstration on the Example of Human Relationship to Nature - Chytrý, Vlastimil; Kroufek, Roman (Scientia in educatione, 2017)
This article is focused on the possibilities in data processing based on the Likert scale. The article outlines the principles guiding the use of data suitable for this particular scale analysis, and then demonstrates how to work with such data sets. The test uses data generated by Nature relatedness scale which is commonly used for analysing the relationship between test subjects and nature with the use of a quantitative method. The main goal of the article is to describe possible ways how to process and analyze such data through the Likert scale survey. In doing so, it also substantiates the procedure of the data processing with reference to empirical data which provide information about man-nature relationship.